Pemberdayaan melalui Zakat Perspektif Al-Qur'an - Mahmuda, Mardan; Sarwan, Sarwan (Jurnal at-Taghyir: Jurnal Dakwah dan Pengembangan Masyarakat Desa, 2020)
Abstract: Zakat serves as a means for muzakki to prosper in many communities. Besides, zakat is also a means for amil zakat in carrying out empowerment activities to realize the welfare of the Islamic community evenly. For this to not only be wishful thinking for the Islamic community, then zakat property needs to be managed well collectively by the government or private institutions according to the instructions of Allah SWT in the Qur'an but still comply with the prevailing laws. The research method used in this study is a qualitative method through a literary study approach. This article is about the definition of empowerment and zakat according to experts, zakat perspective of the Qur'an, community empowerment as well as empowerment of amil zakat perspective of the Qur'an and at the same time contains about the management of zakat according to law number 23 of 2011 which applies in Indonesia. This study is expected to be a contribution for zakat managers such as BAZNAS / UPZ / LAZ including for empowerment agents in managing zakat assets to empower the Islamic community to the maximum and sustainable.Keywords: Empowerment, Zakat, Qur'an